A novel "on-off" electrochemiluminescence sensor for the detection of concanavalin A based on Ag-doped g-C3N4. (1st June 2016) - Fan, Yu; Tan, Xingrong; Ou, Xin; Lu, Qiyi; Chen, Shihong; Wei, Shaping
Abstract: In this work, a novel "on-off" electrochemiluminescence (ECL) biosensor was successfully constructed for ultrasensitive detection of concanavalin A (ConA). The "signal-on" state with strong initial ECL signal was obtained by Ag-doped graphitic carbon nitride nanosheet (Ag-g-C3 N4 ), which was modified onto the glassy carbon electrode (GCE) for immobilizing phenoxy dextran (DexP) through π-π interaction. Then, the target ConA was anchored onto the DexP/Ag-g-C3 N4 modified film via the specific carbohydrate-ConA interaction. Successively, polyaniline-3, 4, 9, 10-perylenetetracarboxylic acid-DexP conjugate (denoted as PANI-PTCA-DexP), as the ECL signal quenching probe, was incubated onto the electrode through the carbohydrate-ConA interaction to achieve the "signal-off" state. Here, PTCA was used as a matrix for the high loading of PANI and DexP, PANI served as the quencher towards Ag-g-C3 N4 system, and DexP as the recognition element for bounding ConA. With the formation of the sandwiched structure of DexP, ConA and PANI-PTCA-DexP, a desirable quenching ECL signal was measured with S2 O8 2− as the co-reactant of Ag-g-C3 N4 . The quenching effect of PANI towards Ag-g-C3 N4 is positively correlated with the concentration of ConA. With such an "on-off" system, the detection of ConA was achieved with a wide linear range from 0.001 ng/mL to 50 ng/mL as well as a low detection limit down to 0.0003 ng/mL.